Penelitian penentuan konstanta saturasi (Ks) pada rbc unit - Prayitno Prayitno (Majalah Kulit, Karet, dan Plastik, 1992)
Kinetic of Rotating Biological Contractor have been investigated by manu researchers. In general the model emploued either saturation kinetic (following Monod equation) or first order kinetic to describe substrate removal. In this experiment, saturation kinetic model was used to find out the saturation constant of the RBC unit. The influent fed into the unit was synthetic waste water with glucose as organic carbon sources. The flow was maintained constant at 20.4 1/d and COD influent resulted the saturation constant (Ks) 11.17 mg/I with 20 hours of detention time.